2018
DOI: 10.4149/bll_2018_063
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between red cell distribution width and mean platelet volume with new onset atrial fibrillation afteroff-pump coronary artery bypass grafting

Abstract: OBJECTIVE: The aim of this study was to evaluate the relationship between red blood cell distribution width (RDW) and mean platelet volume (MPV) with development of postoperative atrial fi brillation (PoAF) after offpump coronary artery bypass grafting (CABG). BACKGROUND: The RDW and MPV have been associated with some cardiovascular disorders. METHODS: A total of 93 patients who underwent off-pump CABG were included in this study. The patients were divided into two groups as developing and nondeveloping PoAF g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…In this study, no correlation was found between preoperative RDW and preoperative MPV values and poAF development. In another previous study, it was found that preoperative RDW and preoperative MPV levels did not have a predictive value for poAF in patients undergoing OPCAB surgery [ 34 ] .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, no correlation was found between preoperative RDW and preoperative MPV values and poAF development. In another previous study, it was found that preoperative RDW and preoperative MPV levels did not have a predictive value for poAF in patients undergoing OPCAB surgery [ 34 ] .…”
Section: Discussionmentioning
confidence: 99%
“…In multivariate analysis, RDW [OR:1.16 (95%CI: 1.0-1.36), P = 0.05] was found to be predictive for PSAF (68.4% sensitivity and 51.2% specificity; P = 0.001). Likewise, Ozsin et al[49] analyzed the RDW levels in 93 patients who underwent off-pump CABG surgery. 24 patients developed PSAF while 69 did not.…”
Section: Description Of Studies Outcomementioning
confidence: 99%
“…Various inflammatory biomarkers such as C-reactive protein, interleukins, and tumor necrosis factor-α have been extensively studied in relation to AF. In addition to these markers, hematological indices obtained from complete blood count (CBC) test such as white blood cell (WBC) 5 , red cell distribution width (RDW) 6 , mean platelet volume (MPV) 6 , neutrophil/lymphocyte ratio (NLR) 7 , and platelet/lymphocyte ratio (PLR) 8 have been investigated as potential prognostic and predictive biomarkers for postoperative new-onset AF.…”
Section: Introductionmentioning
confidence: 99%